COMMUNITY STRUCTURE OF PHYTOPLANKTON IN SEKOTONG AND KODEK BAY WATERS, WEST LOMBOK - Sutomo Sutomo (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
Phytoplankton plays important roles of food weeb in aquatic ecosystem, can absorb and release CO2 which is very useful for other organisms and the environment. The purpose of this research was to study the community structure, including abundance, composition and diversity of phytoplankton in the Sekotong and Kodek Bay, West Lombok. The study was conducted in April 2012 at 10 stations in the Sekotong Bay  and six stations in Kodek Bay. Sampling was done vertically by using plankton Kitahara net having mesh size of 80 μm. The results showed that the abundance of phytoplankton from 10 stations in Sekotong Bay ranged between 834,134-6,488,888 sel/m3, while in Code Bay ranged between 53,571-191,642 sel/m3. Phytoplankton dominant in the waters of Sekotong Bay were Chaetoceros and Skeletonema, while in Kodek Bay the dominant phytoplankton were Chaetoceros, Hemialus, Lauderia, and Skeletonema. The results of the analysis of the diversity of phytoplankton genera in Sekotong Bay  showed the value of diversity index (H')=0.40-1.13 and dominancy  index=0.41-0.85. While in Kode Bay, the diversity of phytoplankton genera showed  the value of diversity index (H')=1.53-1.98 and dominancy index=0.03-0.28. Based on these results, it can be concluded that the diversity of phytoplankton genera in the waters Sekotong Bay could be classified as less to moderate and there was a tendency of being dominated by one genera in the population. The diversity of phytoplankton genera in Kodek could be  classified as moderate and there were low tendency of domination by certain genera in the population. Keywords: stucture community, phytoplankton, Sekotong Bay, Kodek Bay, West Lombok.